IMPLEMENTASI POINT OF SALE BERBASIS AHADPOS UNTUK SISTEM INFORMASI AKUNTANSI PENJUALAN (Pada Apotek Sidowaras Gemolong) - Rizky Alkhusna, Dewi Saptantinah Puji Astuti & Muhammad Rofiq Sunarko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
Sidowaras Pharmacy is a SME engaged in the sale of drugs. The problem is that thesales business process is done manually, making it difficult to know the incomeearned for a certain period. To solve the problem, pharmacies need a system thatcan be oriented to process evidence of transactions, the sale of goods, and makingreports quickly and accurately. One of the information systems oriented is Point ofSale (POS). Selection of this system is done by analyzing the needs of pharmaciesthat is identifying the needs of systems and business processes. After the POSsoftware selection is done, then the one chosen to use is AhadPOS. Implementation isdone by installing and then adjusting the required modules. Further implementedand tested by comparing documents obtained from pharmacies with documentsproduced by the software. Once implemented and tested, it appears that theAhadPOS software can run as required and expected.Keywords: Sales, POS, AhadPOS, Implementation.